MEKANISME PENGKREDITAN PAJAK PERTAMBAHAN NILAI ATAS FAKTUR PAJAK MASUKAN MANUAL - hadining kusumastuti (Universitas Indonesia, 2019)
This final assignment discusses the mechanism of crediting of Input Tax on Manual Tax Invoice by Taxable Enterprise who have used e-Faktur according to Fiskus and response from PT XYZ on SP2DK issued by Fiskus and Crediting Input Tax system according to the prevailing taxation regulation. The results of the analysis can be concluded that according to Fiskus on Manual Tax Invoice cannot be Tax Credit on e-Faktur, while PT XYZ has responded that the transaction opponents has not yet required to issued Electronic Tax Invoice and according to the prevailing taxation regulation, as long as the Tax Invoice fulfilled criterions of Article 9 paragraph (2b) of VAT Law then the Tax Invoice can be a Tax Credit..Keywords: Tax Credit, Taxable Entrepreneur for VAT Purposes, Manual Tax Invoice, electronic Tax Invoice